KINERJA LEMBAGA KEUANGAN MIKRO AGRIBISNIS DI KABUPATEN BANTUL PROVINSI YOGYAKARTA - Yopi Saleh; Chris Sugihono; Vyta W. Hanifah (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACT Performance on Microfinance Institution of Agribusiness in Bantul District Yogyakarta Province. Microfinance Institutions of Agriculture (MIA) has a role in facilitating agricultural financing that grows and develops from the community with a various management. The objective of this study was to determine the performance of the MIA of Rural Agribusiness Development Program (RADP) based on predefined indicators. The study was conducted in March-June 2012 involving 65 MIA-RADP in Bantul district. Primary data were collected through direct interviews using questionnaires with one or all of the board in each of the MIA-RADP. The financial reports in December 2011 used as secondary data. Research approach used the monitoring and evaluation of the scoring method followed by test parameters proportion. The results showed that the performance of the MIA-RADP 2008, 2009 and 2010 in Bantul were fair categorized with improved performance. Increasing the number of clients and a loan portfolio, and also decreasing the levels of NPLs proved this. The results of proportion parameter test showed that there was less than 50% MIA in Bantul district has good performance; the others were in poor and fair category. MIA that worthy as a pilot project is MIA Imogiri stand since 2010. Two approaches to increase the performance of MIA-RADP are: (1) Internal approach that focus on human resource development programs and (2) External approach, that focus on client awareness and optimizing the government role.Keywords : Performance, indicators, MIA, RADPABSTRAKLembaga Keuangan Mikro Agribisnis (LKM-A) berperan memfasilitasi pembiayaan pertanian yang tumbuh dan berkembang dari masyarakat dengan berbagai macam tipe dan pola pengelolaan. Tujuan pengkajian untuk menganalisis kinerja LKM-A Program Usaha Agribisnis Pedesaan (PUAP) berdasarkan indikator yang telah ditetapkan. Penelitian dilakukan pada 65 LKM-A PUAP di Kabupaten Bantul pada bulan Maret-Juni 2012. Pengumpulan data primer dilakukan melalui wawancara langsung menggunakan kuisioner dengan pengurus LKM-A PUAP. Data sekunder ditelusuri dari laporan kegiatan LKM-A per Desember 2011. Analisis data menggunakan metode skoring dan uji parameter proporsi. Hasil analisis menunjukkan bahwa: (1) kinerja LKM-A PUAP tahun 2008, 2009 dan 2010 di Kabupaten Bantul termasuk dalam kategori cukup baik dengan penilaian kinerja yang meningkat, ditunjukkan oleh peningkatan jumlah nasabah dan penyaluran kredit serta menurunnya tingkat Non Personal Loan (NPL), (2) proporsi LKM-A yang memiliki kinerja baik target < 50 persen, selebihnya termasuk kategori cukup dan kurang baik. Upaya untuk meningkatkan kinerja LKM-A PUAP perlu dilakukan dengan pendekatan internal dan eksternal. Pendekatan internal terkait dengan peningkatan SDM pengurus LKM-A yang handal, dan ekternal pada penumbuhan kesadaran nasabah dan optimalisasi peran pemerintah.Kata kunci : Kinerja, indikator, LKM-A, PUAP